The role of the obstetrician-gynecologist and sex educator - Cardinal De San Martin, Cecilia (2015)
The doctor as part of one society has accommodated their thinking and their actions as regards sexuality, thought of the majority. Flipping through the pages of the history of medicine, we noted the richness of thought and innovation capacity in other medical fields, but not in that of sexuality, with a few noted exceptions: Freud, Kraft-Ebbing, Dickinson, Masters Guest facilities and others.